SAT0413 A Case-Control Study of Density and Microstructure at the Distal Radius in Patients with Psoriatic Arthritis. (10th June 2014) - Zhu, Y.; Griffith, J.F.; Qin, L.; Hung, V.W.; Fong, T.-N.; Au, S.-K.; Tang, X.-L.; Kwok, A.W.; Leung, P.-C.; Li, E.K.; Tam, L.-S.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic progressive destructive arthritis characterized by joint inflammation affecting both cartilage and bone. High-resolution peripheral quantitative computed tomography (HR-pQCT) is a noninvasive imaging technique capable of quantitative assessment of volumetric bone mineral density (vBMD) and bone microstructure independently for both cortical and trabecular compartments. Objectives: The objective of the study was to investigate vBMD and bone microstructure at the distal radius in PsA patients. Methods: This cross-sectional study involved 65 PsA patients (30 males and 35 females, age: 54.7±10.4 years; disease duration: 13.8±7.1 years), and 65 age- and gender-matched healthy controls (30 males and 35 females, age: 54.4±10.8). Areal BMD (aBMD) of hip, lumbar spine and ultradistal radius was measured by dual-energy X-ray absorptiometry (DXA). HR-pQCT was performed at the distal radius. Comparisons of density and microstructure indices were performed by analyses of variances with Bonferroni adjustment in post-hoc analyses. Results: PsA patients did not differ significantly from controls in age, body weight and body height. Areal BMD at all measurement sites were similar in PsA patients and controls. Compared to controls, PsA patients had significantly lower cortical volumetric BMD (% between-group difference: -3.93%, p=0.001). Trabecular volumetricBMD and microstructure, including trabecular bone volume fraction, number, thickness and separation, were similar in PsA patients to controls. The only measures indicating compromised bone quality in PsA patients were related to cortical porosity with cortical pore volume (94.9%, p=0.028), porosity index (67.4%, p=0.002) and pore diameter (8.9%, p<0.0001) all significantly higher in PsA patients than in controls. Male and female patients were equally affected although the increase in cortical pore volume (113.4% vs. 84.6%) and cortical porosity index (94.5% vs. 48.8%) was greater in female than male patients. Conclusions: Compromised bone quality in PsA patients is primarily related to increased cortical porosity. This emphasizes the inability of standard areal BMD to explain bone fragility in PsA. References: Zhu TY, Griffith JF, Qin L, Hung VWY Fong TN, Au SK, Tang XL, Kwok AW, Leung PC, Li EK, Tam LS. Structure and strength of the distal radius in female patients with rheumatoid arthritis: A case-control study. J Bone Miner Res 2013; 28(4):794-806. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1843